2021
DOI: 10.1016/j.eclinm.2021.101054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-infection with intestinal parasites on COVID-19 severity: A prospective observational cohort study

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection results in a spectrum of clinical presentations. Evidence from Africa indicates that significantly less COVID-19 patients suffer from serious symptoms than in the industrialized world. We and others previously postulated a partial explanation for this phenomenon, being a different, more activated immune system due to parasite infections. Here, we aimed to test this hypothesis by investigating a potential correlation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 32 publications
(58 reference statements)
3
48
0
1
Order By: Relevance
“…The results of this retrospective study during the COVID-19 pandemic showed that most of the inpatients were patients with severe COVID-19, and the number of outpatients was reduced. Wolday et al ( 2021 ) reported that the patients co-infected with parasites had lower odds of developing severe COVID-19. It has been hypothesized that the low incidence rates of COVID-19 could result from increased exposure to parasites in some countries (Głuchowska et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this retrospective study during the COVID-19 pandemic showed that most of the inpatients were patients with severe COVID-19, and the number of outpatients was reduced. Wolday et al ( 2021 ) reported that the patients co-infected with parasites had lower odds of developing severe COVID-19. It has been hypothesized that the low incidence rates of COVID-19 could result from increased exposure to parasites in some countries (Głuchowska et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that, in parasite endemic areas of COVID-19 cases, the severity of the disease and numbers of deaths decreased mainly due to patient coinfections with parasites, it seems that the effect of some pathogens such as parasites restricting HLA-G expression can be further considered in future studies [ 118 , 119 ]. Unlike other viral or bacterial coinfections that negatively impact respiratory viral diseases such as COVID-19, some parasitic infections could modulate disease severity and the clinical outcome of other infectious diseases such as COVID-19 via intricate molecular networks involving HLA-G, IL-10/TGF-β, and Treg cells [ 103 , 118 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other evidence indicates that COVID-19 lethality rates are significantly lower in Sub-Saharan Africa than in the industrialized world (25). Wolday et al (26) carried out a prospective observational cohort study to investigate whether there was a potential correlation between co-infection with intestinal parasites and the severity of COVID-19 in two sites in an endemic area of Ethiopia in Sub-Saharan Africa. The study revealed that patients co-infected with parasites had lower odds of developing severe COVID-19, with an adjusted odds ratio (aOR) of 0.23 (p < 0.0001) for all parasites, an aOR of 0.37 (p < 0.0001) for protozoa, and an aOR of 0.26 (p < 0.0001) for helminths.…”
Section: Helminth Co-infection and Severity Of Covid-19mentioning
confidence: 99%